ANTIMICROBIAL ACTIVITY OF SOUTH AFRICAN MEDICINAL PLANTS ACCENTUATING ASPECTS RELATING TO METHODOLOGY - van Vuuren, S.; Viljoen, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
A review of the antimicrobial research undertaken on South African medicinal plants validates the traditional medicinal practices used to treat infectious diseases. The various microbiological techniques such as disc diffusion, minimum inhibitory concentration, time-kill and synergy assays commonly used when assessing the antimicrobial activity will be presented with reference to their application in studies on South African medicinal plants. Antimicrobial investigations on extracts are presented where the most active plants are identified from a number of screening studies. Some extracts from indigenous medicinal plants (Croton gratissimus, Tarchonanthus camphoratus) have been selected to demonstrate antimicrobial activity. Antimicrobial activities on the essential oils of some of the most widely used indigenous medicinal aromatic plants are reviewed with emphasis on Osmitopsis asteriscoides and Artemisia afra. A summary of some bioactive compounds, isolated from South African medicinal plants, with antimicrobial activities <200 µg/mL will be presented. A study on Helichrysum cymosum encompassing oil, extract and isolation of a bioactive compound (helihumulone) indicate activities 1– 8 mg/mL, 78 – 313 µg/mL and 16-125 µg/mL respectively. Methods will be critically assessed and recommendations made, based on both literature reviews and practical experience. An overview is given on what antimicrobial activities should be considered noteworthy when reporting on efficacy of extracts, oils and compounds.